Pengaruh Inovasi, Kompetensi Digital, Lingkungan, dan Motivasi terhadap Kinerja Pegawai PU - Ardi Wiranata Hutasoit; Bambang Satriawan; Muamar Khaddafi; John Friadi (Penerbit Goodwood, 2025)
Purpose: This study aims to determine and analyze the effects of the Influence of Innovative Behavior, Digital Competence and Work Environment through Work Motivation on Employee Performance Methodology/approach: The research method used is a quantitative method. This study uses data obtained through questionnaires distributed to employees at the Public Works and Spatial Planning Service of Karimun Regency. The population in this study were 70 civil servants and 18 PPPK employees. This study used 88 respondents. Results/findings: The results of the Hypothesis test show that Digital Competence, Work Environment and Work Motivation do not affect Employee Performance. While Innovative Behavior affects Employee Performance. Digital Competence and Work Environment affect Work Motivation while Innovative Behavior does not affect Work Motivation. Conclusion: Then Digital Competence and Work Environment through Work Motivation do not affect Employee Performance. While Innovative Behavior through Work Motivation affects Employee Performance. Limitations: Generalization of results only applies to ASN and PPPK employees at the Public Works and Spatial Planning Office of Karimun Regency. The use of questionnaires can present subjective bias from respondents. This study may not consider other external factors that affect employee performance. Contribution: With a focus on ASN and PPPK employees at the Public Works and Spatial Planning Office of Karimun Regency. This study adds to the literature related to employee performance studies in the government sector which are often less noticed, especially in the PPPK group.